Pemberdayaan Kelompok PKK dengan Budidaya Sayuran Organik secara Hidroponik Sistem Rakit Apung di Desa Tambaksogra Sumbang Banyumas - Pratama, Rama Adi; Widarawati, Rosi; Sumarni, Eni (Universitas Syiah Kuala, 2024)
The agricultural sector as a source of income for some communities, because most of Indonesia's area is agricultural land. Productive agricultural land is becoming narrower, and the population is increasing, so there is a need for a medium of cultivation that can replace the use of land as a medium for cultivation. One way to use narrow land as an effort to develop agricultural produce, is by hydroponically matching crops. The purpose of this community service is to provide knowledge and to apply hydroponically hydroponic vegetable crops cultivation techniques to the peasant groups in Tambaksogra Village Sumbang Banyumas. The method of implementation of this activity is to provide training, dissemination and support to the peasant group in Tambaksogra Sumbang Banyumas village. The result of the activities that have been carried out is to provide training and support on hydroponic design of shovel rack systems in the use of parkland land, the production of hydro-ponic media, the seeding of hydroponic vegetables, the planting of aquatic spinach, spinach, paccoy and lettuce hydroponically. The activities continued with maintenance up to the harvesting and packaging of hydroponic vegetable crops to become a product with a higher economic value. This activity increases the knowledge of the PKK group about the hydroponic cultivation of vegetable crops in the fountain rackets in the village of Tambaksogra Sumbang Banyumas.